A Recursive Kalman Filter Forecasting Approach - Kahl, Douglas R.; Ledolter, Johannes (Management Science, 1983)
This paper examines the forecasting accuracy and the cost effectiveness of time series models with time-varying coefficients. A simulation study investigates the potential forecasting benefits of a proposed Kalman filter type adaptive estimation and forecasting approach. It is found that: When appropriate, the time-varying coefficient approach leads to better forecasts than the constant coefficient procedures. A simple decision rule, which indicates whether time-varying coefficient models are in fact needed, increases the computational efficiency.